Modulation of iron metabolism by new chemicals interacting with the iron regulatory system - Yoshiaki Tsuji; Jun Ninomiya-Tsuji; Maurice Y.F. Shen; Benjamin R. DiFrancesco (Redox Biology)
Despite the vital role of iron and vulnerability of iron metabolism in disease states, it remains largely unknown whether chemicals interacting with cellular proteins are responsible for perturbation of iron metabolism. We previously demonstrated that cisplatin was an inhibitor of the iron regulatory system by blocking IRP2 (iron regulatory protein 2) binding to an iron-responsive element (IRE) located in the 3′- or 5′-UTR (untranslated region) of key iron metabolism genes such as transferrin receptor 1 (TfR1) and ferritin mRNAs. To guide the development of new chemical probes to modulate the IRP-IRE regulatory system, we used an artificial intelligence (AI)-based ligand design and screened a chemical library composed of cysteine-reactive warheads. Using wild type and mutant IRE-luciferase reporter cells, we identified new IRP-IRE inhibitors such as V004-0872 harboring chloroacetamide, while its analog V011-6261 with chloropropanamide completely lost the inhibitory activity. V004-0872 inhibited the human IRP2 via Cys512 and caused decreased iron levels through reciprocal TfR1 downregulation and ferritin upregulation. V004-0872 increased production of mitochondrial reactive oxygen species (ROS) and exhibited cytotoxicity that was inhibited by N-acetyl cysteine but not the ferroptosis inhibitor ferrostatin-1. Furthermore, we found that widely used haloketone protease inhibitors and acetamide herbicides inhibit the IRP-IRE system. Since IRP2 overexpression is responsible for iron excess conditions to promote growth of several cancers and exacerbation of iron-overload diseases, these results and new compounds lay the groundwork for new reagents and strategies to limit the availability of iron and oxidative stress in iron-overloaded disease conditions.